In defence of epistemic vices. - Bland, Steven (Synthese, 2022)
Vice essentialism is the view that epistemic vices have robustly negative effects on our epistemic projects. Essentialists believe that the manifestation of epistemic vices can explain many of our epistemic failures, but few, if any, of our epistemic successes. The purpose of this paper is to argue that vice essentialism is false. In §1, I review the case that some epistemic vices, such as closed-mindedness and extreme epistemic deference, have considerably beneficial effects when manifested in collectivist contexts. In §2, I add that there are putative epistemic vices whose repeated manifestation leads to significant epistemic achievements over time. Epistemic recklessness is one such unstable vice. Though Sosa argues that epistemically reckless judgements cannot constitute knowing full well, the repeated manifestation of epistemic recklessness is essential to our becoming fully well knowledgeable in the long run. Without making incompetent judgements in environments that offer unambiguous, actionable feedback, we could not develop the intuitive and reflective competences and meta-competences required for knowing full well.